UNCENSORED DEBATE AND THE EVOLUTION OF THE SOVIET MEDIA LANDSCAPE (Spectrum Journal of Innovation, Reforms and Development, 2023)
This article is about the development of Soviet media since 1985 and the increase of uncensored shows. Also, information about Vlasov and his political position, Gorbachev's speeches, significant press coverage is analyzed. In addition, the results of press freedom such as "Lastochka", "Vzglyad" will be discussed.